Psychosocial work strains and well-being in the process of adapting to occupational stress: longitudinal studies of offshore rig workers - Irena Leszczyńska; Aleksandra Peplińska (Health Psychology Report, 2023)
Background The work on offshore rigs is related to a number of physical and mental burdens. The subject matter of the paper refers to the assessment of the relation between the mode of adapting to occupational stress and the feeling of well-being among the employees of offshore rigs in Poland.